The The relationship between history of physical activity and COVID-19 severity with post COVID-19 syndrome - Susy Purnawati; Olivia Theodora; Adiartha Griadhi I Putu; Muliarta I Made (Universitas Udayana, 2025)
Background and purpose: The COVID-19 pandemic has resulted in severe symptoms for many patients, continuing into the formation of post-COVID syndrome which affects the quality of life of patients. This study aims to assess relationship between history of physical activity and COVID-19 severity with post-COVID-19 syndrome. Methods: This was a cross-sectional study involving 87 randomly selected adult COVID-19 patients treated at Udayana University Hospital from January 2022 to December 2023. Data collected were characteristics of the participants, the history of physical activity measured with IPAQ questionnaire, the severity of COVID-19 based on several indicators on the medical records, and post-COVID syndrome assessed with questionnaire. Data analysis method used for the Bivariate test is Chi-Square, and Multivariate uses the Logistic Regression Test to find the relationship between all variables. Results: Of the 87 patients, 56.3% were men with age range from 19 to 56 years. The majority, 83.9% of patients had severe COVID symptoms and 43.7% experienced post-COVID syndrome, with the highest distribution being fatigue, at 81.6%. Low physical activity was associated with post-COVID syndrome (p=0.004), 60.5% patients with low physical activity experience post-COVID syndrome compared to 27.3% with moderate physical activity. A significant relationship was also found between the severity of COVID-19 symptoms and the incidence of post-COVID syndrome (p=0.002). As many as 35.6% of patients who experienced mild COVID-19 experienced post-COVID syndrome, while 85.7% of COVID-19 patients who experienced moderate-severe COVID-19 experienced post-COVID syndrome. The multivariate test also provided significant results between history of physical activity and post-COVID syndrome (p=0.014) and the relationship between COVID-19 severity and post-COVID syndrome (p=0.011). Conclusion: A relationship was found between the history of pre-COVID physical activity and the severity of COVID symptoms with the incidence of post-COVID syndrome. On the other hand, there is no relationship between gender, age and comorbidity with post-COVID syndrome.